The Right to Health in Evidence-based Policymaking - Farah Purwaningrum; Fiona McDonald; Stephanie Doris Short (Jember University Press, 2020)
The right to health is included in United Nations (UN) Sustainable Development Goals (SDG) number 3, “Good health and well-being”. This goal aims to ensure healthy life and to promote well-being for all, at all ages. The SDGs, which build on the Millennial Development Goals (MDGs), provide a significant expansion to the development agenda. Inclusive development is part and parcel of the SDGs. Evidence-based policymaking studies provide explanations of normative and legitimate expectations for policymakers, namely, to use scientific evidence and specific indicators in their policymaking process. The right to health, as constructed, in evidence-based policymaking discourse is in contention. This paper addresses the various types of meaning Indonesian policymakers attach to the right to health through their discourses in norms of health policy. This study provides an analysis of discourses, regulatory analysis, and historical narratives (based on analysis of health regulations and newspaper articles) pertaining to evidence-informed policy in the health sector in Indonesia from 2009-2017. Our findings elucidate how the right to health manifests in the processes of evidence-based policymaking. We do so by way of a two-pronged analysis, i) discourse analysis at the macro level in Indonesia about the right to health as a norm and ii) health policymaking at the micro level, in the Indonesian district of Gunungkidul,within the region of Yogyakarta.